Control and autonomy motivating style: Attitudes and choices of future teachers - Μίχου, Αικατερίνη; Γ. Ματσαγγούρας, Ηλίας (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF